Clinical Practice Guideline: irritable bowel syndrome with constipation and functional constipation in the adult - Fermín Mearin (Revista Espanola de Enfermedades Digestivas)
In this Clinical Practice Guideline we discuss the diagnostic and therapeutic approach of adult patients with constipation and abdominal complaints at the confluence of the irritable bowel syndrome spectrum and functional constipation. Both conditions are included among the functional bowel disorders, and have a significant personal, healthcare, and social impact, affecting the quality of life of the patients who suffer from them. The first one is the irritable bowel syndrome subtype, where constipation represents the predominant complaint, in association with recurrent abdominal pain, bloating, and abdominal distension. Constipation is characterized by difficulties with or low frequency of bowel movements, often accompanied by straining during defecation or a feeling of incomplete evacuation. Most cases have no underlying medical cause, and are therefore considered as a functional bowel disorder. There are many clinical and pathophysiological similarities between both disorders, and both respond similarly to commonly used drugs, their primary difference being the presence or absence of pain, albeit not in an "all or nothing" manner. Severity depends not only upon bowel symptom intensity but also upon other biopsychosocial factors (association of gastrointestinal and extraintestinal symptoms, grade of involvement, and perception and behavior variants). Functional bowel disorders are diagnosed using the Rome criteria. This Clinical Practice Guideline has been made consistent with the Rome IV criteria, which were published late in May 2016, and discuss alarm criteria, diagnostic tests, and referral criteria between Primary Care and gastroenterology settings. Furthermore, all the available treatment options (exercise, fluid ingestion, diet with soluble fiber-rich foods, fiber supplementation, other dietary components, osmotic or stimulating laxatives, probiotics, antibiotics, spasmolytics, peppermint essence, prucalopride, linaclotide, lubiprostone, biofeedback, antidepressants, psychological therapy, acupuncture, enemas, sacral root neurostimulation, surgery) are discussed, and practical recommendations are made regarding each of them.